2021
DOI: 10.1200/jco.2021.39.15_suppl.e16065
|View full text |Cite
|
Sign up to set email alerts
|

HERIZON: A phase 1B/2 open-label study of imu-131 HER2/neu peptide vaccine PLUS standard of care chemotherapy with randomization in phase 2 in patients with HER2/neu overexpressing metastatic or advanced adenocarcinoma of the stomach or gastroesophageal junction.

Abstract: e16065 Background: The phase 2 part of the study hypothesizes HER-Vaxx (IMU-131) will provide treatment benefits consistent with traditional monoclonal antibodies that target HER2 in patients with confirmed Her2+ advanced or metastatic gastric cancer with a corresponding adaptive immune response without added toxicity. In the phase 1b dose finding part of the study tumor response of patients who received 50ug dose strongly correlated with antibody levels with 50ug selected as the phase 2 dose (Wiedermann et. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several tumor vaccines against gastric cancer have been developed, including HER-2-targeted peptide vaccine IMU-131 (HER-Vaxx) (NCT02795988), OTSGC-A24 peptide vaccine (NCT03784040) and MG7-DC vaccine (NCT04567069) ( 128 130 ). While there is currently no FDA-approved tumor vaccine for brain metastasis of gastric cancer, this field shows a broad prospect and is a current research hotspot.…”
Section: Tumor Vaccine Therapymentioning
confidence: 99%
“…Several tumor vaccines against gastric cancer have been developed, including HER-2-targeted peptide vaccine IMU-131 (HER-Vaxx) (NCT02795988), OTSGC-A24 peptide vaccine (NCT03784040) and MG7-DC vaccine (NCT04567069) ( 128 130 ). While there is currently no FDA-approved tumor vaccine for brain metastasis of gastric cancer, this field shows a broad prospect and is a current research hotspot.…”
Section: Tumor Vaccine Therapymentioning
confidence: 99%
“…Besides, there is a correlation between the levels of anti-HER2 antibodies and the clinical response to therapy. In addition, the early data indicated a benefit in OS (hazard ratio of 0.418) with no added toxicity, in association with standardof-care chemotherapy, compared to chemotherapy alone (106). The combination of two peptide B-cell epitope vaccines, representing trastuzumab and pertuzumab binding sites, showed safety and…”
Section: B Cell-based Vaccinesmentioning
confidence: 99%
“…At the time of interim analysis, this study showed an overall survival (OS) benefit with a hazard ratio (HR) of 0.418 (2-sided 80% CI: 0.186, 0.942). Safety, in terms of hematological and non-hematological adverse events, was shown to be similar between the treatment arms with no significant vaccination-related toxicity ( 26 ). Final analysis in the randomized Phase 2 trial showed statistically significant overall survival Hazard Ratio (HR) of 0.585 (80% 2-sided CI: 0.368, 0.930).…”
Section: Introductionmentioning
confidence: 99%